Prevalence, Severity, and Clinical Management of Brain Incidental Findings in Healthy Young Adults: MRi-Share Cross-Sectional Study - Soumaré, Aïcha; Beguedou, Naka; Laurent, Alexandre; Brochet, Bruno; Bordes, Constance; Mournet, Sandy; Mellet, Emmanuel; Pereira, Edwige; Pollet, Clothilde; Lachaize, Morgane; Mougin, Marie; Tsuchida, Ami; et al. (Frontiers in Neurology, 2021)
Background and Objectives: Young adults represent an increasingly large proportion of healthy volunteers in brain imaging research, but descriptions of incidental findings (IFs) in this age group are scarce. We aimed to assess the prevalence and severity of IFs on brain MRIs of healthy young research participants aged 18-35 years, and to describe the protocol implemented to handle them. Methods: The study population comprised 1,867 participants aged 22.1±2.3 years (72% women) from MRi-Share, the cross-sectional brain MRI substudy of the i-Share student cohort. IFs were flagged during the MRI quality control. We estimated the proportion of participants with IFs (any, requiring medical referral, potentially serious [PSIFs] as defined in the UK biobank): overall, by type and severity of the final diagnosis, as well as the number of IFs. Results: 78/1,867 participants had at least one IF (4.2%, 95% Confidence Interval [CI] 3.4-5.2%). IFs requiring medical referral (n=38) were observed in 36/1,867 participants (1.9%, 1.4–2.7%), and represented 47.5% of the 80 IFs initially flagged. Referred IFs were retrospectively classified as PSIFs in 25/1,867 participants (1.3%, 0.9–2.0%), accounting for 68.4% of anomalies referred (26/38). The most common final diagnosis was cysts or ventricular abnormalities in all participants (9/1,867; 0.5%, 0.2–0.9%) and in those with referred IFs (9/36; 25.0%, 13.6–41.3%), while it was multiple sclerosis or radiologically isolated syndrome in participants with PSIFs (5/19; 26.3%, 11.5–49.1%) who represented 0.1% (0.0–0.4%) and 0.2% (0.03–0.5%) of all participants respectively. Final diagnoses were considered serious in 11/1,867 participants (0.6%, 0.3–1.1%). Among participants with referred IFs, 13.9% (5/36) required active intervention, while 50.0% (18/36) were put on clinical surveillance. Conclusions: In a large brain imaging study of young healthy adults participating in research we observed a non-negligible frequency of IFs. The etiological pattern differed from what has been described in older adults.